A Qualitative Study of Multidisciplinary Providers' Experiences With the Transfer Process for Injured Children and Ideas for Improvement. Issue 2 (February 2018) - Gawel, Marcie; Emerson, Beth; Giuliano, John S.; Rosenberg, Alana; Minges, Karl E.; Feder, Shelli; Violano, Pina; Morrell, Patricia; Petersen, Judy; Christison-Lagay, Emily; Auerbach, Marc
Abstract : Objective: Most injured children initially present to a community hospital, and many will require transfer to a regional pediatric trauma center. The purpose of this study was 1) to explore multidisciplinary providers' experiences with the process of transferring injured children and 2) to describe proposed ideas for process improvement. Methods: This qualitative study involved 26 semistructured interviews. Subjects were recruited from 6 community hospital emergency departments and the trauma and transport teams of a level I pediatric trauma center in New Haven, Conn. Participants (n = 34) included interprofessional providers from sending facilities, transport teams, and receiving facilities. Using the constant comparative method, a multidisciplinary team coded transcripts and collectively refined codes to generate recurrent themes across interviews until theoretical saturation was achieved. Results: Participants reported that the transfer process for injured children is complex, stressful, and necessitates collaboration. The transfer process was perceived to involve numerous interrelated components, including professions, disciplines, and institutions. The 5 themes identified as areas to improve this transfer process included 1) Creation of a unified standard operating procedure that crosses institutions/teams, 2) Enhancing "shared sense making" of all providers, 3) Improving provider confidence, expertise, and skills in caring for pediatric trauma transfer cases, 4) Addressing organization and environmental factors that may impede/delay transfer, and 5) Fostering institutional and personal relationships. Conclusions: Efforts to improve the transfer process for injured children should be guided by the experiences of and input from multidisciplinary frontline emergency providers. Abstract : Supplemental digital content is available in the text.